2017
DOI: 10.1186/s12906-017-1567-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and hepatoprotective potential of Lawsonia inermis L. leaves against 2-acetylaminofluorene induced hepatic damage in male Wistar rats

Abstract: Background Lawsonia inermis (Lythraceae) is an ethnomedicinal plant, traditionally known for curing several ailments such as skin diseases, bacterial infections, jaundice, renal lithiases and inflammation etc. The present work deals with assessment of in vitro antioxidant and in vivo hepatoprotective potential of butanolic fraction (But-LI) of Lawsonia inermis L. leaves.MethodsAntioxidant activity was evaluated using deoxyribose degradation, lipid peroxidation inhibition and ferric reducing antioxidant power (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 81 publications
1
12
0
1
Order By: Relevance
“…The results of this study showed that exposure to cadmium causes a significant increase in membrane lipid peroxidation in the liver and kidneys of rats but pretreatment with aqueous leaves extract of Vitex doniana was effective in the prevention of oxidative damage induced by cadmium, which resulted in significantly lower degree of lipid peroxidation in the liver and kidneys. This is consistent with the previous studies in which natural plant products effectively reduced lipid peroxidation induced in response to various toxicants [36,37,38]. This can be explained by the important role of polyphenols in preventing lipid peroxidation and in the protection of the integrity and functioning of tissues and cells.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study showed that exposure to cadmium causes a significant increase in membrane lipid peroxidation in the liver and kidneys of rats but pretreatment with aqueous leaves extract of Vitex doniana was effective in the prevention of oxidative damage induced by cadmium, which resulted in significantly lower degree of lipid peroxidation in the liver and kidneys. This is consistent with the previous studies in which natural plant products effectively reduced lipid peroxidation induced in response to various toxicants [36,37,38]. This can be explained by the important role of polyphenols in preventing lipid peroxidation and in the protection of the integrity and functioning of tissues and cells.…”
Section: Discussionsupporting
confidence: 93%
“…The liver enzymes, aspartate aminotransferase (ASAT), alanine aminotransferase (ALAT), are routinely used to evaluate liver function; they are considered markers of hepatocellular health [ 34 ]. The elevated level of these enzymes is a marker of liver pathology and might be attributed to Alloxan’s action [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Kumar et al [40] have shown following a thiobarbituric lipid peroxidation inhibition test (TBARS) of the butanolic fraction of Lawsonia inermis leaves (But-LI), a moderate inhibition of 58.90% at the maximum concentration (1000 μg/mL) and 39.33% at the lowest concentration (100 μg/mL). The But-LI fraction had a higher IC50 (375.73 μg/mL) than the standard Trolox (IC50 = 136.47 μg/mL).…”
Section: Discussionmentioning
confidence: 99%